Reduction with age in methylcytosine in the promoter region −224∼−101 of the amyloid precursor protein gene in autopsy human cortex - Tohgi, Hideo; Utsugisawa, Kimiaki; Nagane, Yuriko; Yoshimura, Masahiro; Genda, Yasuko; Ukitsu, Miyuki (Brain research. Molecular brain research., 1999)
Methylation status of cytosines and its changes with age in the promoter region (−226∼−101) of the amyloid precursor protein (APP) was analyzed using bisulfite genomic sequencing in the cerebral cortex of human autopsy brain. Cytosines at 13 locations were methylated in at least one of the cases studied. Methylcytosines at these locations was more frequent in cases ≤70 years old (26%) than in cases >70 years old (8%) ( p<0.05). Cytosines at −207, −204, −200, and −182 are frequently methylated, and the frequency of methylcytosine in these locations was significantly higher in cases ≤70 years old (55%) than cases >70 years old (5%) ( p<0.01). These cytosines constituted one of the 9-bp-long GC-rich elements (GGGCGC G/A GG) or an 11-bp inverted repeat (GGCCGT CGGCC). The present findings indicate that some cytosines, particularly those at −207∼−182, in the promoter region of the APP gene are frequently methylated and suggest that their demethylation with age may have some significance in the development of Aβ deposition in the aged brain. The relative importance of these elements in the total promoter activity of the APP gene remains to be definitively established.